A new method for function-loss based seismic resilience assessment of buildings. (1st September 2022) - Jiang, Huanjun; Bu, Haifeng; He, Liusheng
Highlights: Function loss is quantified by assembling with fuzzy theory and logic trees. A general repair scheme is developed to get time-varying function recovery. Seismic resilience of buildings is assessed by quantifying an integrated index. Abstract: Seismic resilience assessment of buildings is an important aspect in developing resilient buildings. To evaluate seismic resilience of general buildings directly and quickly using a comprehensive index, a new framework of seismic resilience assessment for buildings by assembly-based function loss quantification is developed. Considering the fuzziness uncertainty in evaluation, a new method quantifying function loss of buildings is firstly proposed by consequence analysis of components, logic trees connected with fuzzy operators, and logic system of buildings including relevance between stories. Then the repair scheme of buildings is proposed to compute the time-varying function loss of buildings during the whole recovery process. The proposed method is embedded in probabilistic performance-based earthquake engineering (PBEE), in which uncertainty factors during the whole life cycle of buildings can be considered. Case study on a ten-story RC moment-resisting frame building is provided to demonstrate the applicability of the proposed method. Results show that the case building's resilience index can be easily and reasonably computed by the proposed framework at different earthquake intensity levels. Compared with the existing assembly-based function methods and resilience assessment methods, the proposed method avoids subjectivity during evaluation greatly. The proposed resilience assessment method can help to develop resilient buildings.